AUDIO-LINGUAL METHOD AS METHOD IN IMPROVING SPEAKING ABILITY OF SECOND SEMESTER OF ENGLISH DEPARTMENT STUDENTS OF UNRIKA - Herawati, Netty (Universitas Riau Kepulauan, 2012)
Audio-lingual approach in teaching of speaking at the second semester of English Department of University of Riau Kepuluan is significant. When they know the meaning of audio-lingual approach, it mean the students got motivation to be more active inÂ learning. They can interpret than audio-lingual approach was good achievement of the speaking improvement.Teaching by using audio-lingual approach to the students can be used here, because this procedure could be use to introduce the English language. These usages represent the kinds of knowledge units we store plus the link ages, or relation between knowledge units. Knowledge of the relationship between learning with another learning is very important not only for learner the meaning English language but also for the developing the ability to react. In other word, for developing native like competence in the English language.